Shared Religious Soundscapes: Indian Rāga Music in Jewish, Christian, and Islamic Devotion in South Asia - Guy L. Beck (Religions, 2023)
Music has played a central role in Indian religious experience for millennia. The origins of Indian music include the recitation of the sacred syllable OM and Sanskrit Mantras in ancient Vedic fire sacrifices. The notion of Sound Absolute, first in the Upanishads as Śabda-Brahman and later as Nāda-Brahman, formed the theological background for music, Sangīta, designed as a vehicle of liberation founded upon the worship of Hindu deities expressed in rāgas, or specific melodic formulas. Nearly all genres of music in India, classical or devotional, share this theoretical and practical understanding, extending to other Indic religions like Buddhism, Jainism, and Sikhism. What is less documented is how rāga music has been adopted by non-Indic communities in South Asia: Judaism (Bene Israel), Christianity (Catholic), and Islam (Chishti Sufi). After briefly outlining the relation between religion and the arts, the Indian aesthetics of Rasa, and the basic notions of sacred sound and music in Hinduism, this essay reveals the presence of rāga music, specifically the structure or melodic pattern of the morning rāga known as Bhairava, in compositions praising the divinity of each non-Indic tradition: Adonai, Jesus, and Allah. As similar tone patterns appear in the religious experiences of these communities, they reveal the phenomenon of “shared religious soundscapes” relevant to the comparative study of religion and music, or Musicology of Religion.